Dorsal root ganglion stimulation relieves chronic neuropathic pain along with a decrease in cortical γ power - Morgalla, Matthias Hubert; Zhang, Yi; Chander, Bankim Subhash (Neuromodulation, 2024)
Background - Stimulation of dorsal root ganglion (DRG) is an ideal neuromodulative intervention, providing pain relief in localized chronic pain conditions because γ-band oscillations reflect the intensity of ongoing chronic pain in patients affected. - Objective - We aimed to observe the role of cortical γ-band power associated with the relief of chronic neuropathic pain through DRG stimulation (DRGS). - Materials and Methods - We examined nine patients (two women, mean age 56.8 years; range, 36-77 years) diagnosed with chronic neuropathic pain who underwent DRGS therapy. We used the numeric rating scale (NRS) on the painful limb and simultaneously recorded the electroencephalography to assess the broadband γ power. Assessments were conducted on the first day and on the seventh day after implantation of the DRGS system and then compared and correlated with the results of the NRS. - Results - The NRS scores showed a significant decrease from the first day to the seventh day (p = 0.007). The resting-state γ power revealed a significant decrease (p = 0.021) between 30 and 45 Hz, recorded through the central electrode contralateral to the painful limb from the first day (mean [M] = 0.46, SD = 0.25) to the seventh day (M = 0.31, SD = 0.12) after DRGS. There was no significant change in the resting-state γ-band power recorded through the central electrode ipsilateral to the painful limb. However, we found a positive correlation in the γ-band power (rs = 0.628, p = 0.005) with the NRS rating. - Conclusions - A lateralized decrease in broadband γ power may be considered further evidence supporting a reduction in the hyperexcitability of the nociceptive system in response to DRGS therapy. In the future, γ-band power could serve as a biomarker for assessing the efficacy of DRGS during the seven-day test phase preceding the implantation of the DRGS system.
Online verfügbar: 27. März 2024, Artikelversion: 4. Juli 2024
Gesehen am 20.01.2025